Economic and Institutional determinants of financial development for bank dominated and stock market-based economies in the SADC region - Mogale, Etumeleng (University of the Witwatersrand, Johannesburg, 2022)
The study examines the determinants of financial development from the bank-dominated economies (Angola, Lesotho and Madagascar) versus the bank and stock market-based economies’(Mauritius, Namibia and South Africa) point of view for the selected SADC countries. The study further examines which economies develop more over time between economies that are bank-dominated and those that have both the banking sector and the stock markets. Using a panel dataset that spans from 1996 to 2018 - which was sourced from the World Development Indicators (WDI) - the study utilized the Autoregressive Distributive lag (ARDL) techniques to separately model for the banking system and the stock market which allowed for the unpacking of any short-run and long-run contributors to the financial sector development and thus capture any possible links between the explanatory variables and the financial development proxies, domestic credit to the private sector and market capitalization. The study found that the banking sector development is influenced by GDP growth rate, foreign direct investment, governments debts, trade openness and the rule of law while the stock markets are largely driven by GDP growth rate, inflation, trade openness, rule of law and regulatory quality. Furthermore, the study found that the banking sector does benefit from the presence of stock markets and that over time economies with both financial sectors tend to develop more than bank-dominated economies and that they are less prone to external shocks. The contributions to the existing body of literature are by critically looking at the drivers or deterrents of financial development in the SADC region so that the appropriate policy prescriptions can be formulated and implemented with the broader view of closing the infrastructure gap that exists within the region. By separately modelling the two financial sectors the study was able to see indicators that are the driving force in each sector and which economies – bank-dominated vs stock market-based - tend to do well over time.
A Research Report presented for the degree of Master of Economics Science at the School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2022
Keywords: Financial development; Stock markets; Bank system; Financial markets; Regress; Trade opennes; SADC; GDP growth; UCTD; SDG-8: Decent work and economic growth